Development of low temperature stoichiometric solution combustion derived transparent conductive ternary zinc tin co-doped indium oxide electrodes. Issue 76 (13th October 2017) - Pujar, Pavan; Gandla, Srinivas; Singh, Mukesh; Gupta, Bikesh; Tarafder, Kartick; Gupta, Dipti; Noh, Yong-Young; Mandal, Saumen
Abstract : Here, the development of transparent conductive zinc tin co-doped indium oxide (IZTO: In1.4 Sn0.3 Zn0.3 O3 ) ternary electrodes is addressed through low temperature solution combustion processing. Abstract : Here, the development of transparent conductive zinc tin co-doped indium oxide (IZTO: In1.4 Sn0.3 Zn0.3 O3 ) ternary electrodes is addressed through low temperature solution combustion processing. Optimization of fuel to oxidizer ratio offers low temperature (∼130 °C) of combustion with balanced redox reaction. The thin films of IZTO annealed at different temperatures showed a decreasing trend in the resistivity with a fixed order of 10 −2 Ω cm and the film with a highest Hall mobility of 5.92 cm 2 V −1 s −1 resulted at 400 °C. All the films with different temperatures of annealing were smooth (rms ≤ 2.42 nm) in nature and the IZTO film annealed at 200 °C is 83% transparent in the visible spectra. The effective band gap of 0.9 eV determined from first-principles density functional theory gives clear evidence for the conducting nature of IZTO. The thin film transistor fabricated with IZTO as a gate electrode with poly(methyl methacrylate) and pentacene as the dielectric and channel material, respectively, exhibited a saturation mobility of 0.44 cm 2 V −1 s −1 and I on / I off ratio of 10 3 . Further, the printability of the IZTO combustible precursor is established which resulted in anti-edge deposition of the printed feature.